Parent–Child Adaptive Responses for Digital Resilience - John P. Ziker; Jerry Alan Fails; Kendall House; Jessi Boyer; Michael Wendell; Hollie Abele; Letizia Maukar; Kayla Ramirez (Social Sciences)
This research investigates U.S. parents’ responses to the rapidly changing, novel environment of the internet, applying evolutionary theory and interdisciplinary methodologies. Novel environments pose potential challenges to existing adaptive strategies, so this research investigates important questions about how parents and children perceive the risks of children’s entry into the virtual world and how they mitigate potential risks. The research focuses on parents of children in middle childhood (children ages 6–12), a significant period in human life history when children start building relationships outside the family. We utilize in-depth interviews (n = 26), cultural domain analysis (n = 32), surveys (n = 199), and participatory co-design (n = 34) to synergize theoretical concepts in evolutionary anthropology with the applied research focus of human–computer interaction. Cultural domain maps and interview results identify and classify perceptions of costs, benefits, and risks, including intrinsic and extrinsic sources of risk and risk tangibility. Survey results further identify platforms and risks of highest priority and confirm parental interest in new kinds of tools for managing the digital experiences of their children. Life history theory informs our approach to the development of parental control software that favors skill building and encourages parent–child discussions supporting child executive function and resilience to risks.